The use of Wavelight® Contoura to create a uniform cornea: the LYRA Protocol. Part 1: the effect of higher-order corneal aberrations on refractive astigmatism - Motwani M (Dove Medical Press, 2017)
Manoj Motwani Motwani LASIK Institute, San Diego, CA, USA Purpose: To demonstrate how higher-order corneal aberrations can cancel out, modify, or induce lower-order corneal astigmatism. Patients and methods: Six representative eyes are presented that show different scenarios in which higher-order aberrations interacting with corneal astigmatism can affect the manifest refraction. WaveLight® Contoura ablation maps showing the higher-order aberrations are shown, as are results of correction with full measured correction using the LYRA (Layer Yolked Reduction of Astigmatism) Protocol. Results: Higher-order corneal aberrations such as trefoil, quadrafoil, and coma can create ovalization of the central cornea, which can interact with the ovalization caused by lower-order astigmatism to either induce, cancel out, or modify the manifest refraction. Contoura processing successfully determines the linkage of these interactions resulting in full astigmatism removal. Purely lenticular astigmatism appears to be rare, but a case is also demonstrated. The author theorizes that all aberrations require cerebral compensatory processing and can be removed, supported by the facts that full removal of aberrations and its linkage with lower-order astigmatism with the LYRA Protocol has not resulted in worse or unacceptable vision for any patients. Conclusion: Higher-order aberrations interacting with lower-order astigmatism is the main reason for the differences between manifest refraction and Contoura measured astigmatism, and the linkage between these interactions can be successfully treated using Contoura and the LYRA Protocol. Lenticular astigmatism is relatively rare. Keywords: topographic guided ablation, LASIK, PRK, WaveLight Contoura, uniform cornea, higher order aberrations